Use of Tissue Expander for Contracted Scarred Saddle Deformity Rhinoplasty - Ostby, Erin; Inman, Jared; Ardeshirpour, Farhad (Facial Plastic Surgery, 2019)
The main purpose of this article is to present an alternative technique for the reconstruction of saddle nose deformity in patients with severely scarred or contracted soft tissue envelopes. In this single surgeon case series, the authors present a two-staged reconstruction performed on four adult patients with saddle nose deformities and contracted soft tissue envelope stemming from a variety of etiologic factors including vasculitis, sarcoidosis, and trauma. Stage one involved placement of a 1 × 4 cm tissue expander along the nasal dorsum through anterior scalp and endonasal incisions. The tissue expander port was positioned under the anterior scalp and injected with saline over 3 weeks in-office. Stage two involved removal of the tissue expander and rhinoplasty using osteocartilaginous rib grafts. All four patients had successful expansion of the contracted soft tissue envelope, creating adequate space for the newly reconstructed nasal framework. One patient developed exposure of the tissue expander through the endonasal incision, which did not lead to any adverse outcome. All patients in this series tolerated expansion well, without complaints of pain or external skin breakdown. The use of soft tissue expanders along the nasal dorsum can successfully expand contracted and scarred soft tissue envelopes prior to reconstructive rhinoplasty. This technique may be an effective alternative to the use of interpolated flaps in treating these patients.
Keywords: rhinoplasty; saddle nose deformity; nasal reconstruction; tissue expander; revision rhinoplasty